Multilateralism before the interdict and the crossroad - Montalvo, Mauricio (2016)
This article examines how the US decision to attack Iraq goes against both the nature of multilateralism and the rules of international law. The “preventive action” and the “confrontation between good and evil” are seen as the main milestones of the US's international vision. The author argues for the necessity of a renewal of multilateralism so that it does lose its validity.